2016
DOI: 10.3945/an.115.010538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flavonoids on Upper Respiratory Tract Infections and Immune Function: A Systematic Review and Meta-Analysis

Abstract: Previous research on animals indicates flavonoid compounds have immunomodulatory properties; however, human research remains inconclusive. The aim of this systematic review was to assess the efficacy of dietary flavonoids on upper respiratory tract infections (URTIs) and immune function in healthy adults. A created search strategy was run against Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE and EMBASE classic, CINAHL, and AMED. The returned studies were initially screened, and 2 reviewers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 49 publications
1
85
0
1
Order By: Relevance
“…Although several studies have examined the effects of dietary supplements on immune function in man [ 9 , 10 ], few have evaluated relationships between medicinal plants and immune function in human subjects. A recent systematic review and meta-analysis demonstrated the beneficial effects of plant flavonoids on upper respiratory tract infections and immune function [ 11 ]. Another clinical trial reported that the water extract of the roots of Eurycoma Longifolia favorably influenced immune parameters, such as total T cell, CD4 + T cell, and naïve T cell counts [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have examined the effects of dietary supplements on immune function in man [ 9 , 10 ], few have evaluated relationships between medicinal plants and immune function in human subjects. A recent systematic review and meta-analysis demonstrated the beneficial effects of plant flavonoids on upper respiratory tract infections and immune function [ 11 ]. Another clinical trial reported that the water extract of the roots of Eurycoma Longifolia favorably influenced immune parameters, such as total T cell, CD4 + T cell, and naïve T cell counts [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with systemic inflammation and oxidative stress and one explanation is poor diet (Manna & Jain 2015;Osadnik et al 2019). Meta-analyses show that vitamin D supplementation, antioxidant flavonoid intake and probiotics decrease the incidence of respiratory infections, which supports our findings that vitamin availability and oxidative stress affect antiviral immunity (Martineau et al 2017;Quick 2015;Somerville, Braakhuis & Hopkins 2016). A diet high in antioxidants may benefit antiviral immunity, and additionally, limited data show that it could alleviate asthma symptoms (Wood et al 2008).…”
Section: Discussionsupporting
confidence: 70%
“…Regarding individual athletes, the risk of developing Covid-19 can be reduced by regular sleep, eating a wellbalanced diet, and staying well hydrated, to maintain the capacity of the immune system [28]. A proper intake of fruit and vegetables (7-8 portions per day) is beneficial, since these foods contain polyphenols and flavonoids that support immune function [29]. Athletes with asthma should use their prescribed medications meticulously to reduce the risk for a more serious course of illness.…”
Section: Recommendations For Sports Health During the Sars-cov-pandemicmentioning
confidence: 99%